Factors influencing land title registration practice in Osun State, Nigeria. Issue 3 (9th October 2017) - Ekemode, Benjamin Gbolahan; Adegoke, Oluseyi Joshua; Aderibigbe, Adetunji
Abstract : Purpose: The registration of land titles is an important component of title documentation and certification process that is influenced by a variety of factors. The purpose of this paper is, therefore, to examine factors influencing land title registration practice in Osun State, Nigeria. Design/methodology/approach: Data used for this paper were collected from 520 land title registration applicants, representing 48.10 per cent of the total number of applicants for land title/property rights registration in Osun State, Southwestern Nigeria, using systematic random sampling technique, with sampling interval k = 5. Data collected were analyzed using descriptive and inferential statistical techniques, such as frequency distribution and percentages, relative importance index (RII) and factor analysis. Findings: The findings revealed that factors such as high cost of title documentation and corrupt practices of land registry staff had significant influence on land title/property rights registration process, while factors such as suitability of organizational structure and personnel competence/low morale had less influence on land title registration in the study area. Practical implications: The findings of this paper suggest the inadequacies inherent in the land title registration process in the study area which has significant implications for land titling registration process in Osun State, the entire Nigerian state and other emerging African economies. Originality/value: The paper is one of the few papers that analyzed the factors influencing land title registration from the perspective of end-users in an emerging African economy like Nigeria.